Development of Yogurt Analogue by Blending Soy-Maize Milk (Tribhuvan University Journal of Food Science and Technology, 2022)
The aim of this research was to develop yogurt analogue by blending soy-maize milk and to study its sensory and keeping quality. D-optimal mixture design was employed for the formulation of soy-maize yogurt analogue. Five different formulations containing soymilk and maize milk in the ratio of 100:0, 85:15, 70:30, 55:45 and 40:60 were prepared. Sugar (6 g per 100 g milk base), xanthan gum (0.005 g per 100 g milk base) and culture (2U per 20 l) were mixed in all formulations. The prepared yogurts were subjected to sensory evaluation for consumer acceptability. The sensory analysis revealed that soymilk (85%) and maize milk (15%) was of acceptable quality. There was significant difference (p